Economic Warfare - Daniel Spiro (Center for Economic Studies and ifo Institute (CESifo), 2023)
What actions should we expect countries to take when engaged in economic warfare? This paper first shows that the goal of winning a war implies a very simple and intuitive objective of economic warfare: maximize one's own less the opponent's (weight-adjusted) payoff. This objective function is then applied to a number of canonical strategic economic environments showing how warfare transforms them. In a warfare-equilibrium between a buyer and a seller, the traded quantity is lower than in peace but, surprisingly, the price may be lower. The analysis shows when trade will altogether collapses in war and when trade will persist between the parties despite it. A prisoner's-dilemma game (e.g., monopolistic competition or climate-change mitigation) remains a prisoner's-dilemma game also in war, and cooperation may be impossible also under infinite repetition. A coordination game with heterogeneous preferences (e.g., choosing technological standard) in war collapses to either deliberate miscoordination or to 'matching pennies' where one country is trying to imitate the other which is trying to avoid this. The results are interpreted through the lens of the current economic warfare between Russia and the West.
Keywords: C72; D74; F51; 330; economic warfare; conflict; sanction; trade